CRIMINAL LAW ENFORCEMENT OF URUK SOIL WITHOUT MINING BUSINESS LICENSE (IUP) - Erlando, Angga Riki Argo; Prawesthi, Wahyu; Amiq, Bachrul (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
The government has the authority to control and guarantee the availability of natural resources for the benefit of society. Within its authority, the government has regulated and provided guidelines for the exploitation of natural resources in the mining sector in Indonesia through Law No. 4 of 2009 concerning Mineral and Coal Mining (Minerba Constitution). This research aims to determine criminal liability and criminal law enforcement of the mining of uruk soil without a Mining Business License (IUP). The method used in this research is normative legal research. The results showed that several conditions must be filled for a person or legal entity to be sentenced, including the existence of a criminal act committed, the ability to be responsible and the element of error of intentionality or negligence. As stipulated in article 158 of the Law of the Republic of Indonesia number 4 of 2009 concerning Mineral and Coal mining. Law enforcement by the police of the Directorate of Special Criminal Investigation of East Java Regional Police, through investigation, has succeeded in finding suspects on behalf of supono or supo. Based on witness statements, expert statements, suspect statements, and evidences, it have fulfilled the criminal elements of mining uruk and sand land without being equipped with a Mining Business License (IUP) as stipulated in article 158 of RI Law number 4/2009 concerning Mineral and Coal mining.